Food cultural code in british linguoculture (using concepts ‘bread’ and ‘milk’ as examples) - Galynska, Olena (My University, 2018)
Food is an essential and ancient element of the material culture. Each nation is formed in certain natural conditions and is gradually adapting for them. Food traditions of a nation are formed in dependence to certain conditions:natural, geographical, historical, etc.Phraseologisms with concepts "bread" and "milk" are analysed from the linguocultural view.
Keywords: food; cultural code; linguoculture; concept bread; культурний код; лінгвокультура; кафедра іноземних мов професійного спрямування